사물인터넷 응용을 위한 암호화 프로세서의 설계 - 안재욱; Jae-uk Ahn; 최재혁; Jae-hyuk Choi; 하지웅; Ji-ung Ha; 정용철; Yongchul Jung; 정윤호; Yunho Jung (한국항행학회논문지, 2019)
최근 IoT 산업에서 보안의 중요성이 증가하고 있으며, IoT (internet of things) 통신 산업에서는 소형의 하드웨어 칩이 필요하다. 이를 위해 본 논문에서는 대표적인 블록 암호 알고리즘인 AES (advanced encryption standard), ARIA (academy, research, institute, agency)와 CLEFIA를 통합한 저면적 암호화 프로세서를 제안한다. 제안하는 암호화 프로세서는 128 비트 기반으로 라운드 키 생성 과정과 암호화 및 복호화 과정을 하나로 공유하였으며, 각각 알고리즘의 구조를 공유시켜 면적을 축소하였다. 더불어, 경량 IoT 기기를 포함한 대부분의 IoT 기기나 시스템에 적용이 가능하도록 구현하였다. 본 프로세서는 Verilog HDL (hardware description language)로 기술되었고 65nm CMOS 공정을 통해 논리 합성하여 11,080개의 논리 게이트로 구현 가능함을 확인하였다. 결과적으로 각 알고리즘 개별 구현대비 gate 수 총계에서 약 42%의 이점을 보인다. Recently, the importance for internet of things (IoT) security has increased enormously and hardware-based compact chips are needed in IoT communication industries. In this paper, we propose low-complexity crypto-processor that unifies advanced encryption standard (AES), academy, research, institute, agency (ARIA), and CLEFIA protocols into one combined design. In the proposed crypto-processor, encryption and decryption processes are shared, and 128-bit round key generation process is combined. Moreover, the shared design has been minimized to be adapted in generic IoT devices and systems including lightweight IoT devices. The proposed crypto-processor was implemented in Verilog hardware description language (HDL) and synthesized to gate level circuit in 65nm CMOS process, which results in 11,080 gate counts. This demonstrates roughly 42% better than the aggregates of three algorithm implementations in the aspect of gate counts.